Morphological analysis of breast cystic lesions in shear wave elastography - Rzymski, Paweł; Opala, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Breast cancer is still a great cause of concern in oncology, with high prevalence. Besides mammography, ultrasonography, and magnetic resonance imaging, elastography is an imaging technique recently developed and offers new breast imaging possibilities, mapping breast elasticity. The aim of our study was to evaluate the morphology of cystic breast lesions with special attention to quantification of Young moduli distribution and possible modification of the morphological elastographic score in breast lesions. Material and methods : Eighteen breast cystic lesions were evaluated in patients aged 26-55 (36.6 ±8.8) with sonography, shear wave elastography and fine needle biopsy. Results : All lesions were diagnosed as benign cysts. The difference between glandular tissue stiffness and cystic lesion residual stiffness was not statistically significant (p = 0.64). But comparing the cystic lesion with the area under the cyst and margin, the difference was statistically significant (p < 0.001 and p = 0.025 respectively). The differences in stiffness heterogeneity between cyst and glandular tissue, margin and area under the cyst were significant (p < 0.001; p = 0.014; p = 0.017 respectively). The mean percentage of area within the lesion with detectable shear wave propagation was 61.6% (10-100%). The percentage of detectable propagation within the lesion negatively correlated with lesion volume (Rs = –0.65, p = 0.003). Also lesion elastographic heterogeneity correlated negatively with cyst volume (Rs = –0.53, p = 0.02). Conclusions : Shear wave elastography predicts breast cysts with characteristic morphology. Further research to compare it with malignant lesions is needed.